To review the transient osteoporosis of the hip due to a case report - Case Report - Ömer Faruk Şendur; Gülcan Gürer; Ayşe İyiyapıcı (Galenos Yayinevi, 2006)
Transient osteoporosis of hip is a rare disease of unknown etiology. It is usually seen in middle-aged men and women in the third trimester of pregnancy and is associated with hip pain. It typically runs a benign course with eventual resolution of symptoms. In this paper, a male patient with a complaint of left hip pain which was diagnosed as transient osteoporosis of the hip was presented by reviewing current literatures. (Osteoporoz Dünyasından 2006; 12 (1): 15-17)